Elementos a serem considerados na concessão de crédito ao consumidor - Mendonça, Luis Geraldo (2002)
The purpose of this work is to analyze the elements required by the financiai institutions for concession of credit in financing cars to customers. The study is based in the recovery of already living concepts, as well as in the development of new techniques, aiming the analysis of the risks evolved in this kind of operation, regarding the importance of this segment for financiai institutions. Regarding objectives, the methodology used, was exploratory research, for it is a subject of little technical knowledge in Brazil, and methodological itself, for it is necessary to know the procedures and techniques in order to achieve the target. Regarding the means, field research will be used to demonstrate how institutions act nowadays and their perspectives, as well as bibliographic research, regaining the existent analytical instrumental. A methodology based on reliable and straight elements, applied to thís segment of the market, will result in a process much more selective of the clients, which will contribute for the improvement of results in those financing institutions, through the decrease of the risks in their accounts.